ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL OPERASI PECAHAN BENTUK ALJABAR SMP - Jesisca L T Mangi; Elsy Senides H Taunu; Mega Retno Wulandari; Anggriati Ledu Ngaba; Yuliana Tamu Ina Nuhamara; Mayun Erawati Nggaba (Program Studi PGSD Universitas Flores, 2022)
According to the national examination (UN) scores for Junior High School in East Sumba in 2019, it can be seen that the percentage of student’s math scores based on the comparison of test scores with graduation standards is still very low. In view of the problem, studies are conducted to describe a student’s error, describing the factors that cause students to make mistakes in solving problems, and planning follow-up actions to minimize student errors when operating addition and subtraction of algebraic fraction. This type of research is qualitative approach. The technique of determining the student’s research subject uses the cluster sampling technique with sample 5 students. The technique of collecting data is done by writing tests, interviews and documentary studies. The results showed that according to Newman’s five types of errors, student made 5 types of errors, and the most common mistakes were in encoding error of 1,53%, then processing skill error 2,33%; transformation error 2,5%; comprehension error and reading error 3,1%.